Tata Kelola Kota Layak Anak: Sebuah Analisis Bibliometrik - Nila Wahyuni (Institut Ilmu Sosial dan Manajemen STIAMI, 2023)
This study aims to analyze the scientific literature on child-friendly city governance using the Bibliometric Analysis framework. Analysis using VOSviewer software version 1.6.19 with database from Google Scholar. The search for articles uses Publish or Perish software version 8, assisted by the Mendeley Desktop software version 1.19.8 in completing the article data. The keywords used in the search were